Samsoniella doupengshanensis, a new species from Guizhou, China - Zeng, Qian; Chen, Xu; Chen, Wan-Hao; Tian, Wei-Yi (Phytotaxa, 2025)
A new species, Samsoniella doupengshanensis, isolated from an infected pupa, is introduced. Morphological comparisons and DNA-based phylogenies from analysis of a multigene dataset of combined ITS, LSU, RPB2 and TEF sequences support establishment of the new species. It differs from other species by its shorter phialides, smaller ellipsoidal conidia and pupa host.